The structure of Scots pine and Black locust forests in the Northern Steppe of Ukraine - Lovynska, Victoria; Ловінська, Вікторія Миколаївна; Sytnyk, Svitlana; Ситник, Світлана Анатоліївна (Чеська академія сільськогосподарських наук, 2016)
The article describes the distribution of areas of Scots pine (Pinus sylvestris Linnaeus) and Black locust (Robinia pseudoacacia Linnaeus) stands within the Northern Steppe of Ukraine based on forest biometry data. The total area of Scots pine stands is 21,472.9 ha, of Black locust it is 17,683.7 ha, which corresponds to 24.6 and 26.9% of the total forest-covered area. Scots pine is partly naturally, partly artificially regenerated. Black locust stands are man-made forests only. Both species form mainly pure stands within the study area. Mean age of Scots pine is around 60 years with a mean wood stock of 292 m3.hа-1. The dominant Black locust stands are overmature ones with a mean age of 43 years and a mean stock of 149 m3.hа-1. Generally, for both species, an increase in mean wood stock was observed, reaching its maximum at 71 to 75 (Scots pine) and 81-85 (Black locust) years of age. It has been demonstrated that the largest area of Black locust stands is represented by relatively rich soil conditions (54.3%), whereas in Scots pine stands there are relatively poor soils (56.5%). У статті описано розподіл площ насаджень сосни звичайної ( Pinus sylvestris Linnaeus) і акації ( Robinia pseudoacacia Linnaeus) у межах Північного Степу України за даними лісової біометрії. Загальна площа насаджень сосни звичайної становить 21472,9 га, акації – 17683,7 га, що відповідає 24,6 та 26,9% загальної лісистості. Сосна звичайна частково відновлена природним шляхом, частково штучно. Насадження акарини – це лише рукотворні ліси. Обидва види формують переважно чисті насадження в межах досліджуваної території. Середній вік сосни звичайної становить близько 60 років із середнім запасом деревини 292 м 3 •га -1 . Домінуючими акаціями є перестійні насадження із середнім віком 43 роки та середнім запасом 149 м 3 •га -1 . Загалом для обох видів спостерігалося збільшення середнього запасу деревини, що досягало максимуму у віці 71–75 (сосна звичайна) та 81–85 (акара) років. Показано, що найбільша площа насаджень акації представлена відносно багатими ґрунтовими умовами (54,3%), тоді як у насадженнях сосни звичайної – відносно бідними (56,5%).
Структура лісів сосни звичайної та акарину Північного Степу України
Keywords: forest fund; лісовий фонд; wood stock; деревний запас; indexes of forest biometrics; індекси лісової біометрії; forest-forming species; лісоутворюючі породи; age structure; вікова структура; functional categories of forest; функціональні категорії лісу